2022
DOI: 10.4000/interventionseconomiques.16665
|View full text |Cite
|
Sign up to set email alerts
|

Latin American Health Regimes in the Face of the Pandemic

Abstract: Les régimes de santé latino-américains face à la pandémie Los regímenes de salud latinoamericanos ante la pandemia Ilán BizbergWith the collaboration of Mauricio Jiménez Hernández.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Márquez-González et al [27], Carrillo-Vega et al [51], and Salinas-Escudero et al [52] analyzed the national database to identify the risk factors for hospitalization and death in the Mexican population, showing a lower patient survival rate among those hospitalized in public institutions. This problem is prevalent among health systems in most LAC countries, which, to varying degrees, all lack universal public health regimes, instead relying heavily on private subsystems and, in most cases, considerable out-of-pocket expenses [32,[53][54][55]. In their cohort study of a private healthcare network in Brazil, De Oliveira et al also reported a considerably lower mortality rate compared with other cohorts from the public subsystem in Brazil and other parts of the world [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Márquez-González et al [27], Carrillo-Vega et al [51], and Salinas-Escudero et al [52] analyzed the national database to identify the risk factors for hospitalization and death in the Mexican population, showing a lower patient survival rate among those hospitalized in public institutions. This problem is prevalent among health systems in most LAC countries, which, to varying degrees, all lack universal public health regimes, instead relying heavily on private subsystems and, in most cases, considerable out-of-pocket expenses [32,[53][54][55]. In their cohort study of a private healthcare network in Brazil, De Oliveira et al also reported a considerably lower mortality rate compared with other cohorts from the public subsystem in Brazil and other parts of the world [5].…”
Section: Discussionmentioning
confidence: 99%
“…Latin America and the Caribbean (LAC) has arguably been one of the areas most impacted by the pandemic, five of the region's countries being among the 20 with the highest number of reported cases and deaths [30,31]. The pandemic has had a very elevated socioeconomic impact on the region, particularly affecting vulnerable populations: groups with a high poverty index or a lack of formal employment [21,31] as well as those with preexisting comorbidities, exacerbated by deficiencies of the health institutions in vulnerable countries [32], with most of these regions being unable to guarantee public healthcare to a considerable percentage of the population. As a response to the lack of complete public coverage, health systems in countries such as Mexico are forced to rely heavily on private spending [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study may thus be reflecting the effects of problems existing in the dental sector labour market prior to the pandemic, especially in southern Brazil, where this study took place and where, after the southeast, most of Brazil's dentists are concentrated 32 . The findings, which are grounded in the concepts of the theoretical models applied 33,34 , help to explain, in part, socioeconomic points of view on occupa-tional stress among dentists, which was aggravated during COVID-19.…”
Section: Discussionmentioning
confidence: 84%
“…In Latin America, the pandemic defeated not only the health systems but also the historical model of Iberian American societies without universal social protection regimens 32,33 . Health systems in the region need to be organized practically under the principle of Health for All, but rather Health for Some 34 .…”
Section: The Structural Postponement Of Forecasting Attention By Deve...mentioning
confidence: 99%
“…Porque en Latinoamérica la pandemia derrotó no sólo a los sistemas de salud, sino al modelo histórico de sociedades iberoamericanas sin regímenes de protección social universales 32,33 . Los sistemas de salud de la región no están organizados en términos prácticos según el principio de Salud para Todos, sino de Salud para Algunos 34 .…”
Section: La Postergación Estructural De La Atención De Predicciones P...unclassified